Reported incidence of fever for under-5 children in Zambia: a longitudinal study. Issue 1 (December 2015) - Hamooya, Benson; Chongwe, Gershom; Sitali, Lungowe; Halwindi, Hikabasa
Abstract Background Childhood fever is the most common clinical sign ofPlasmodium falciparum infection. It is used as a measure of burden of the disease and the effectiveness of control programs for malaria. This study aimed to determine the incidence of fever in under-5 children of Magoye and Chivuna rural areas of Mazabuka district, Zambia. Methods Incidence of fever was evaluated longitudinally over a period of 16 months (July 2006 and November 2007) among children aged 12–59 months in Magoye and Chivuna rural communities. The data was collected for a study on community directed treatment of soil-transmitted helminth infections in under-five children. Data from caretakers of 1221 children were collected using a structured interviewer-administered questionnaire. Cox proportion hazard regression was used to determine predictors of multiple episodes of fever and Kaplan-Meier survival curves was used to compare survival between two groups. Results A total of 1221 under-5 children [median age 32 months; IQR 12–58] participated in the study and 696 (57 %) were from Magoye and 525 (43 %) from Chivuna. The incidence rate of fever was 162.4 per month per 1000 children for the 16 months period. The proportion of fever was not statistically related to children' age [p  = 0.779] and sex [p  = 0.546]. Predictors of multiple episodes of fever were: age (37–48 vs. 12–24 months) [HR 0.81; 95 % CI 0.67, 0.98;p  = 0.030]; location (Chivuna vs. Magoye) [HR 1.35; 95 % CI 1.17, 1.56;p  < 0.001]; and season (dry vs. rainy) [HR 0.17; 95 % CI 0.12, 0.23;p  < 0.001]. Conclusion The study has shown that the incidence of fever was high in the study areas. Febrile illnesses like malaria still have a significant effect on the health of under-5 children in the study population. There still exists the need for interventions aimed at reducing the incidence of fever in under five children, more especially in rural areas.